2023
DOI: 10.48084/etasr.5687
|View full text |Cite
|
Sign up to set email alerts
|

Controller Design based on Fractional Calculus for AUV Yaw Control

Abstract: This research presents a fractional order integral controller strategy, which improves the steering angle for Autonomous Underwater Vehicles (AUVs). The AUV mathematical modeling is presented. A Fractional Order Proportional Integral (FOPI) control scheme is implemented to ensure the yaw angle stability of the AUV steering under system uncertainty. The FOPI controller is validated with MATLAB/Simulink and is compared to the conventional Integer Order PI (IOPI) controller to track the yaw angle of the structure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…For the robotic arm structure, it is crucial for the controller to track the desired position accurately in order to attain a stable operation. Noninteger calculus is a generalized concept to fractional order differential and integral basic operator ^# _ ` as defined in [17]:…”
Section: Model Parametersmentioning
confidence: 99%
“…For the robotic arm structure, it is crucial for the controller to track the desired position accurately in order to attain a stable operation. Noninteger calculus is a generalized concept to fractional order differential and integral basic operator ^# _ ` as defined in [17]:…”
Section: Model Parametersmentioning
confidence: 99%
“…Active control techniques are used in VC systems against instability modes [5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Active control techniques can be used in both the towing vehicle and the caravan system.…”
Section: Introductionmentioning
confidence: 99%
“…Model-based and model-independent methods are used in active control techniques developed using ADB in VC systems. The Model Predictive Control (MPC) controller was developed to increase the lateral stability of the trailer system and prevent the occurrence of unstable situations [7,[21][22]. Examining the performance of the braking controller using the Linear Quadratic Regulator (LQR) technique showed that stable responses were produced [4,6,22].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations